Implementation of the Pump Irrigation Program in Improving Rice Crop Productivity at the Agricultural Extension Center of Barru District, Barru Regency - Jumria; Wahyul AZ (P3M Stia Al Gazali Barru and Meraja media, 2025)
[Full Paper] to pdf Copyright (c) 2025 Meraja journal